2014
DOI: 10.1515/dma-2014-0026
|View full text |Cite
|
Sign up to set email alerts
|

Generating functions and the Myerson vector in communication networks

Abstract: Cooperative games on undirected graphs are considered. The characteristic function is de ned in a special way with due account of the number of links and distances between vertices (players). An imputation procedure is put forward for a tree graph, the resulting imputation is shown to agree with the Myerson vector. For its calculation the use of the generating function is proposed. It is shown that the results obtained may be extended to games with arbitrary graphs. Note: Originally published in Diskretnaya Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…Characteristic function (payoff of coalition S) can be determined in different ways. Here we use the approach of [10,11,14,15], which is based on discounting directed paths. The payoff to an individual player is called an imputation.…”
Section: Myerson Cooperative Game Approachmentioning
confidence: 99%
“…Characteristic function (payoff of coalition S) can be determined in different ways. Here we use the approach of [10,11,14,15], which is based on discounting directed paths. The payoff to an individual player is called an imputation.…”
Section: Myerson Cooperative Game Approachmentioning
confidence: 99%
“…where σ k (i) is a number of the paths of the length k which include i. In [15] it is proven that this allocation rule for unweighted graphs is the Myerson value. The Myerson value for player i depends on the number of paths that it lies on.…”
Section: Centrality Measure For Weighted Network Using Myerson Valuementioning
confidence: 99%
“…But computing the Myerson value is not an easy problem. In the paper [15] a sufficiently simple procedure was proposed to calculate the Myerson value for a cooperative game on the unweighted graph with special characteristic function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The imputation of the general payoff in this cooperative game can be used for ranking of players and, respectively, for nodes of the graph. In [17] for the communication game with special characteristic function it was proposed a fairly simple imputation procedure based on the generating function and was shown that the resulting imputation agrees with the Myerson value. The advantage of the Myerson value is in taking into account the impact of all coalitions.…”
Section: Introductionmentioning
confidence: 99%